Fracture maturity controls the complexity of earthquake rupture: evidence from source processes of six moderate earthquakes during swarm activities off the east coast of Izu Peninsula, Japan - Yukako Tanaka; Takuji Yamada (Earth, Planets and Space)
Abstract Volcano-tectonic earthquake swarms associated with the intrusion of volcanic fluids have been occurring intermittently off the east coast of the Izu Peninsula, Japan. In this study, we estimated the source processes of the six largest earthquakes (Mw 3.9–5.6) that occurred in this region in 2006 and 2009 and investigated their characteristics with respect to areas of swarm activities. We first selected waveforms of smaller earthquakes (Mw3.4–3.9) as empirical Green’s functions and carried out the waveform inversion with 200 time windows for two horizontal components of 10-s-long K-net waveforms. Individual time windows had a duration of 0.2 s and a spacing of 0.05 s. We fixed the total seismic moments to those determined by the National Research Institute for Earth Science and Disaster Resilience of Japan (NIED) and investigated the temporal characteristics of the moment rate functions. We found that two out of the six earthquakes had complex rupture characteristics and that those events took place in an area that had been inactive in terms of swarms for a couple of decades, suggesting that the complexity of these earthquake ruptures was controlled by the maturity of the fractures formed as a result of swarm activities in the region. Graphical Abstract